Nature Inspired Antimicrobial Nanotextured Surfaces - Yee Lin Tan (Molecular Frontiers Journal, 2020)
The development of cross infections arising from bacteria transmission on frequently touched facilities has led to an urgent need to promptly disinfect these surfaces, such as hand railings, door handles and elevator buttons. Conventional antimicrobial disinfectants are not ideal as they contribute to the growing antimicrobial resistance crisis. In recent years, the discovery that the wings of insects such as the Clanger cicada (Psaltoda claripennis) possess naturally occurring antimicrobial properties has led to a growing interest to synthetically recreate these surfaces. The use of a physical contact killing mechanism on such nanotextured surfaces is a promising strategy for curbing the proliferation of bacteria, as it is unlikely to contribute to the formation of antimicrobial resistance. Here, I highlight the key advantages of using these antimicrobial nanotextured materials and how they could play a role in safeguarding public health security, especially during the current COVID-19 pandemic.